2004
DOI: 10.4049/jimmunol.173.2.1240
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni Worms Induce Anergy of T Cells via Selective Up-Regulation of Programmed Death Ligand 1 on Macrophages

Abstract: Infectious pathogens can selectively stimulate activation or suppression of T cells to facilitate their survival within humans. In this study we demonstrate that the trematode parasite Schistosoma mansoni has evolved with two distinct mechanisms to suppress T cell activation. During the initial 4- to 12-wk acute stages of a worm infection both CD4+ and CD8+ T cells are anergized. In contrast, infection with male and female worms induced T cell anergy at 4 wk, which was replaced after egg laying by T cell suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
155
5
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(170 citation statements)
references
References 58 publications
(44 reference statements)
4
155
5
2
Order By: Relevance
“…Recent studies suggest that these cell surface molecules may be important in macrophagemediated T cell suppression. In particular, PD-L1 expressed by macrophages following S. mansoni infection can trigger T cell anergy in vitro following interactions with PD-1 [37].…”
Section: Control Of Inflammationmentioning
confidence: 99%
“…Recent studies suggest that these cell surface molecules may be important in macrophagemediated T cell suppression. In particular, PD-L1 expressed by macrophages following S. mansoni infection can trigger T cell anergy in vitro following interactions with PD-1 [37].…”
Section: Control Of Inflammationmentioning
confidence: 99%
“…We have developed a model of short term in vitro culture of distinct cell populations with live worms (18). Spleen cells from a naive mouse were cultured with 15 live worms in Transwells for 48 h at 37°C.…”
Section: Passive Transfer Of In Vivo or In Vitro Modulated B Cellsmentioning
confidence: 99%
“…Adult worms were cultured as previously described (18). In brief, adult schistosome worms were obtained 8 wk postinfection by portal perfusion as previously described (24).…”
Section: In Vitro Worm Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Similar to CTLA4, its enhanced expression supports our finding that FhTeg induces anergenic like T cells. In other studies PD1 and its ligand PD-L1 has been shown to play a role in T-cell hyporesponsiveness seen during S. mansoni infection [12,31] and also was elevated during filariasis [13,29] . PD1 expression is also associated with T-cell exhaustion [32], which is mostly centered on CD8 + T cells.…”
mentioning
confidence: 99%